Innovations in natural dye production: bridging tradition and modern technology - Shailendra Yadav; Shailendra Yadav; Harish Chandra Prajapati; Sankatha P. Sonkar; Rama Shankar Nigam; Rishikesh Chandravanshi; Chitrasen Gupta (Frontiers in Plant Science)
Natural dyes have a rich historical significance, rooted in traditional practices that utilize plant materials, minerals, and organic substances to produce vibrant pigments. However, their use declined with the advent of synthetic dyes in the 19th century due to challenges in scalability, cost, and color consistency. Recent advancements in sustainability and modern technology have reignited interest in natural dyes, offering innovative solutions to overcome historical limitations. This review highlights traditional and contemporary extraction techniques, including solid-phase micro extraction, supercritical fluid extraction, pressurized-liquid extraction, and microwave-assisted extraction. Additionally, cutting-edge approaches such as grinding-assisted microwave irradiation and enzymatic extraction methods are examined for their ability to enhance yield, efficiency, and environmental sustainability. These modern techniques enable the utilization of unconventional sources, including agricultural waste and invasive species, thereby promoting sustainable dye